THE ROLE OF MODERN ANTIBIOTICS IN THE PREVENTION OF INFECTIOUS COMPLICATIONS AFTER EXTRACAPSULAR CATARACT EXTRACTION - Nigmatjonova Nozima; Oralov Behruz Abdukarimovich (Web of Journals Publishing, 2025)
Extracapsular cataract extraction (ECE) is widely used in ophthalmic surgery, especially in resource-limited countries. However, despite advances in surgical technology, inflammatory complications, particularly infectious endophthalmitis, continue to pose a serious clinical problem. The purpose of this review article is to conduct a comparative analysis of the efficacy of the antibacterial drugs Levofloxacin (Levoximed) and Tobramycin in the prevention of postoperative complications in EEC. The review is based on the data of modern clinical and microbiologic studies for the last ten years. Levofloxacin was found to have a broader spectrum of action, better tissue permeability and lower flora resistance. The presented data confirm its clinical advantage as a first-line drug in antibacterial prophylaxis after ophthalmic interventions.
Keywords: Extracapsular cataract extraction, postoperative complications, endophthalmitis, Levofloxacin, Tobramycin, antibacterial prophylaxis, ophthalmic surgery.